2016
DOI: 10.3174/ajnr.a4716
|View full text |Cite
|
Sign up to set email alerts
|

Brain Injury in Neonates with Complex Congenital Heart Disease: What Is the Predictive Value of MRI in the Fetal Period?

Abstract: BACKGROUND AND PURPOSE Brain injury in neonates with congenital heart disease is an important predictor of adverse neurodevelopmental outcome. Impaired brain development in congenital heart disease may have a prenatal origin, but the sensitivity and specificity of fetal brain MR imaging for predicting neonatal brain lesions are currently unknown. We sought to determine the value of conventional fetal MR imaging for predicting abnormal findings on neonatal preoperative MR imaging in neonates with complex congen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 35 publications
0
48
0
Order By: Relevance
“…A large number of studies have indicated that associated chromosomal abnormalities, most commonly trisomy, are present in about 2.8% of IVM cases. Recent studies addressing the risk of trisomy 21 have highlighted that idiopathic VM is present in 0.15% of euploid fetuses and in 1.4% of trisomy 21 fetuses, providing a likelihood ratio of 9 for aneuploidy risk .…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have indicated that associated chromosomal abnormalities, most commonly trisomy, are present in about 2.8% of IVM cases. Recent studies addressing the risk of trisomy 21 have highlighted that idiopathic VM is present in 0.15% of euploid fetuses and in 1.4% of trisomy 21 fetuses, providing a likelihood ratio of 9 for aneuploidy risk .…”
Section: Discussionmentioning
confidence: 99%
“…However, the predictive value of brain abnormalities detected in utero MRI on postnatal preoperative brain injury is limited. Further postnatal studies prior to cardiac surgery are needed (41). In newborns with complex CHD prior to surgery (4246), smaller preoperative brain volumes, abnormal brain metabolism and decreases in cortical folding, and gyral development were also detected.…”
Section: Encephalopathy Of Chd: Delayed Maturation Injury and Neuromentioning
confidence: 99%
“…Fetal MRI can also be used to assess lung parenchymal lesions and airway compromise in CHD and has been used to demonstrate the presence of pulmonary lymphangectasia in a fetus with hypoplastic left heart syndrome, an important prognostic finding . MRI of the fetal brain may provide crucial information to clinicians and parents regarding medium‐term and long‐term prognoses, which may have a profound effect on both prenatal and postnatal management independent of the underlying cardiac diagnosis …”
Section: Discussionmentioning
confidence: 99%
“…These innovations will not only help to bring prenatal cardiovascular MRI closer to its postnatal counterpart but could also offer the potential to enhance our fundamental understanding of the nature and aetiology of congenital heart defects – including challenging prenatal diagnoses such as coarctation of the aorta – and their interactions with other organ systems such as the placenta and the developing fetal brain . The incorporation of all of the above techniques is the subject of ongoing research within our departments.…”
Section: Discussionmentioning
confidence: 99%